Implementasi Pendidikan Islam Moderat Pada Masyarakat Urban Metropolitan di SMA Tahfidz Khairunnas Gunung Anyar Surabaya - Ummil Fida Thaha; Maftuh Maftuh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study highlights the significant role of students at SMA Tahfidz Khairunnas Surabaya in promoting the values of moderate Islam within the urban metropolitan context of Surabaya. The findings demonstrate that the implementation of moderate Islamic education is reflected in four core principles: At-Tawazun (balance), At-Tawasuth (moderation), At-Tasamuh (tolerance), and Al-Adl (justice). These values are supported by the family, school, and community environment, which collectively contribute to shaping students’ understanding and practice of moderation. The results further suggest that fostering moderate Islamic values in metropolitan society requires both maturity and contextual comprehension, enabling communities to internalize and apply these principles effectively. The involvement of students in disseminating moderate values represents an essential step toward strengthening critical thinking, moral integrity, and social ethics in accordance with Islamic moderation. Therefore, the educational practices at SMA Tahfidz Khairunnas not only contribute to individual student development but also serve as a catalyst for cultivating a more harmonious, tolerant, and balanced urban society.